Answer:
Inverse function are symmetric with respect to line y=x.
It can be written as:
and
![f^(-1)(f)(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5iimvighj8qrp26j1qdhhe3z5jko8tt8dl.png)
Let's rewrite the given function notation by using y term.
f(x) = 6x-1
i.,e y = 6x-1
Let's solve this equation for x;
Add 1 to both sides we get;
y+1 =6x
Divide both sides by 6 we get;
![x = (y+1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ljjpv65xqvca2l0zmn2f7so8x0rd7tmncc.png)
Now, switch the "x" and "y" we have;
![y= (x+1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dne9wlq66yemoawcjbrjbnaodvkvx0dubb.png)
In the function notation:
![f^(-1)(x) =(x+1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v6r510ntsxfpf4edk7tz93r8911gzqpzfy.png)